Generalized sixth-order gravity and inflation - Amendola, Luca (Classical and quantum gravity, 1993)
The authors consider sixth-order theories of gravity with Lagrangians containing the term R N Square Operator R, where N>1 is an integer. A conformal transformation gives a picture with two scalar fields in Einstein's theory. They find de Sitter and power law inflationary solutions. However, the theory has an unstable weak-field behaviour, because the linearized field equation is of lower order than the non-linear one.
Gesehen am 21.11.2017